10. Didactic Method of Learning during Music Lessons - Applicable in Distance Learning - Hudáková Jana; Králová Eva (Sciendo, 2022)
The development of contemporary modern technologies in the field of music education is advancing forward. Our contribution points out to the use of didactic method of learning in music lessons with a focus on tablets. The importance of tablet as a modern teaching aid is significant in terms of pupils' motivation in education of contemporary elementary school. We focus on the classification of teaching aids and didactic techniques and their appropriate selection and analysis. In our survey we use a questionnaire as a method to find out how effective is the use of didactic techniques by selected Slovak teachers. We conclude the contribution synthesizing the knowledge from the nationwide project School at a Touch.